Trimethoprim-metformin interaction and its genetic modulation by OCT2 and MATE1 transporters - Grün, Barbara; Kießling, Michael; Burhenne, Jürgen; Riedel, Klaus-Dieter; Weiß, Johanna; Rauch, Geraldine; Haefeli, Walter E.; Czock, David (British journal of clinical pharmacology, 2013)
Aims Metformin pharmacokinetics depends on the presence and activity of membrane-bound drug transporters and may be affected by transport inhibitors. The aim of this study was to investigate the effects of trimethoprim on metformin pharmacokinetics and genetic modulation by organic cation transporter 2 (OCT2) and multidrug and toxin extrusion 1 (MATE1) polymorphisms. Methods Twenty-four healthy volunteers received metformin 500 mg three times daily for 10 days and trimethoprim 200 mg twice daily from day 5 to 10. Effects of trimethoprim on steady-state metformin pharmacokinetics were analysed. Results In the population as a whole, trimethoprim significantly reduced the apparent systemic metformin clearance (CL/F) from 74 to 54 l h−1 and renal metformin clearance from 31 to 21 l h−1, and prolonged half-life from 2.7 to 3.6 h (all P < 0.01). This resulted in an increase in the maximal plasma concentration by 38% and in the area under the plasma concentration-time curve by 37%. In volunteers polymorphic for both OCT2 and MATE1, trimethoprim had no relevant inhibitory effects on metformin kinetics. Trimethoprim was associated with a decrease in creatinine clearance from 133 to 106 ml min−1 (P < 0.01) and an increase in plasma lactate from 0.94 to 1.2 mmol l−1 (P = 0.016). Conclusions The extent of inhibition by trimethoprim was moderate, but might be clinically relevant in patients with borderline renal function or high-dose metformin.